Evaluación ambiental de extracción de caliza, minería Artesanal no metálica, en zona de amortiguamiento – Bosque de protección Alto Mayo, Rioja –2010 - Delgado Alvarez, Gianina (2011)
This research paper provides a methodological proposal for environmental assessment for the development of the artisanal mining non-metallic activity (Limestone), located in the Elias Soplin Vargas District , Rioja Province, San Martin Department, near to the Santa Fe Center Rural village, within the Buffer Zone of the Alto Mayo Protection Forest - BPAM, and area of mining concessions. The methodology used by the Concessionary Holder, for the identification and quantitative evaluation of environmental potential impacts was based on the use of the interactive counterfoil modified of Leopold. For the assessment of the potential environmental impacts only used the characterization of the impact as a function of his nature ( +) and ( - ), more did not take into account other criteria. The environmental study submitted by the incumbent concessionaire, specifies how final result of the assessment and evaluation of the potential environmental impacts that will cause the project an assessment 6.0 as the final result which asserts a level of impact according to the table rock climbing OBTIMO LOW. Obtaining a positive result can be that the analysis was not performed taking into account that the area of implementation of the project is a buffer zone and the respective allocations typological of impacts, in order to measure the incidence of the same on the environmental units impacted; tilting action Control, mitigation, and prevention in the Environmental Management Plan. The methodological proposal product of the research project is based on an array of environmental assessment of double-entry LEOPLOD, which took into account all the activities impacting that can take place due to the project; subsequently for each action is considered all the environmental factors that might be affected significantly by giving a weighting quantitatively and qualitatively with two types of impacts: Magnitude: it comes to be the valuation of the impact to being provoked, preferring a sign (+) ó (-) and Importance: That comes to be the value ponderal, that gives the relative weight of the potential of every impact. Product of the application of the methodology indicated it was established that higher potential environmental impacts negative will generate the construction phase. reaching maximum values of -5.71 of magnitude and 4.71 of importance; as well as in the stage of the operation, reaching maximum values of -7 in magnitude and 7 in importance, in this sense the holder concessionaire will have to reformulate their environmental assessment, and in the light of this you will have to implement mitigation measures (M), Control ( C), prevention (P), in each of the activities impacting to guarantee the effectiveness and use of the resource to be exploited.